Bolivia : Staff Report for the 2012 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Well-balanced macroeconomic policies, accompanied by an improvement in terms of trade during recent years, have allowed Bolivia to achieve very positive macroeconomic results. The 2012 Article IV Consultation highlights that the outlook for 2012 is favorable and short-term downside risks are manageable. Real gross domestic product (GDP) is expected to continue growing at a fast pace, reflecting still high terms of trade and mildly expansionary policies. The external current account and the fiscal balance are expected to remain in surplus.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet